When working together goes against common sense: a framework to bridge conservation and agricultural perspectives in participatory working lands research - Hailey Wilmer; Ryan Wilbur; John Derek Scasta; Molly C. Levy; Vicken Hillis; Gregory Newman; David W. Pellatz; Lauren M Porensky (Ecology and Society)
As biodiversity conservation becomes more urgent and the links between wildlife and rural well-being become more apparent, conservation researchers increasingly seek to engage with partners in agricultural communities through participatory approaches. A central hypothesis in participatory research is that inclusive, co-produced research facilitates more relevant, usable, and credible knowledge that can inform real-world decision-making processes, such as those that shape the management of rangelands. But how can conservation scientists more effectively collaborate with agricultural communities when dealing with divisive topics where collaboration appears to go against the common sense of distinct social groups? This paper aims to draw lessons for effective participatory working lands research (PWR) from a participatory prairie dog research project in the USA. We explore the Prairie Dog/Cattle Weight Gains (PDCWG) project in the Thunder Basin Ecoregion of east-central Wyoming, USA, to (1) synthesize the participatory methods scholarship into a conceptual framework for understanding the PWR context; (2) apply this framework to the specific experiences of the PDCWG project; and (3) develop an associated list of activities researchers can use to put these insights into practice in other PWR contexts. Our analysis reveals how social-ecological context shapes the ways in which different actors (researchers or participants) experience PWR. Awareness of social-ecological context and critical reflection on individual and group backgrounds can foster sincere, authentic, and creative research collaborations that support the well-being and goals of diverse participants and communities. We offer a suite of activities PWR practitioners can use to foster awareness of historical conflict context and collaboration, distinct mental models of the system, ecological dynamics, and ownership in research.